Effect of Holiday Periods on Obstetrician’s Cesarean Desicions - Kıran, Gürkan; Menekşe Güven, Alanur; Ekerbiçer, Hasan Çetin; Köstü, Bülent; Arpacı, Haldun (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To compare the cesarean sections performed prior to public holidays in 2004 with the rates of cesarean deliv ery in other periods in Kahramanmaraş. STUDY DESIGN: A total of 3994 cesarean sections out of 11611 deliveries were analyzed retrospectively. Two different long public holiday periods were determined. The total number of cesarean deliveries in a total of ten days comprised of each five days prior to the mentioned holiday periods were taken into consideration and evaluated. RESULTS: No significant difference was found in these units between the numbers of cesarean deliveries in periods prior public holiday dates and the numbers of cesarean in other times. CONCLUSIONS: As a result of this study, it may be concluded that the tendency of physicians in cesarean indications before long off-time periods is not as effective as expected. Further detailed studies examining also the indications of cesarean sections with larger patient populations are required to make a real conclusion.